2009
DOI: 10.1007/s10592-008-9780-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of admixture between differentiated genetic pools at a regional scale in an invasive carnivore

Abstract: Invasive species represent a major threat to biodiversity, and the understanding of their population genetics is one of the most important goals in conservation biology. Recently, it has been proposed that methods using molecular tools could help define efficient eradication strategies and should be a preliminary step in the management process. The American mink was introduced in Europe for fur farming purposes in the 1920s, and, due to escapees, several feral populations have been mentioned in the last decade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The American mink, alternatively called Neovison vison or Mustela vison (we will refer to this taxon as N. vison), has been utilized as a source of fur from both wild-caught and captive-reared animals (Kidd et al 2009;Bifolchi et al 2010). The utilization of so-called farmed animals in fur production in North America and Europe has resulted in feral populations formed from escaped individuals.…”
Section: American Minkmentioning
confidence: 99%
See 2 more Smart Citations
“…The American mink, alternatively called Neovison vison or Mustela vison (we will refer to this taxon as N. vison), has been utilized as a source of fur from both wild-caught and captive-reared animals (Kidd et al 2009;Bifolchi et al 2010). The utilization of so-called farmed animals in fur production in North America and Europe has resulted in feral populations formed from escaped individuals.…”
Section: American Minkmentioning
confidence: 99%
“…In Europe, where escaped populations of the non-native N. vison can be viewed as an invasive species, a different scenario has been detected. Specifically, Bifolchi et al (2010) reported that the genetic makeup of feral populations of American mink in Brittany reflected hybridization and introgression among genetically divergent lineages. This pattern of admixture was likely a reflection of both inbreeding in the farmed populations leading to divergent subpopulations that then escaped and also the history of introductions of captive animals from North America that derived from three separate N. vison subspecies (Bifolchi et al 2010).…”
Section: American Minkmentioning
confidence: 99%
See 1 more Smart Citation
“…In North America, the escapee populations have introgressed with natural populations of N. vison, leading to concerns over the conservation of the native populations. Specifically, Bifolchi et al (2010) reported that the genetic makeup of feral populations of American mink in Brittany reflected hybridization and introgression among genetically divergent lineages. Thus, hybridization between the escaped and wild populations could lead to the genetic extirpation of the native gene pool, or alternatively, the production of novel lineages that form the basis of further evolutionary innovation (Arnold 1997(Arnold , 2006Seehausen 2004).…”
Section: American Minkmentioning
confidence: 99%
“…For example, in two populations in Ontario (Canada) consisting of escaped, wild, and hybrid mink, Kidd et al (2009) detected only 36 % wild individuals, with the remainder being hybrid (10 and 46 %) or escaped genotypes. This pattern of admixture was likely a reflection of both inbreeding in the farmed populations leading to divergent subpopulations that then escaped and also the history of introductions of captive animals from North America that derived from three separate N. vison subspecies (Bifolchi et al 2010). In Europe, where escaped populations of the non-native N. vison can be viewed as an invasive species, a different scenario has been detected.…”
Section: American Minkmentioning
confidence: 99%